1999
DOI: 10.1111/j.1365-2141.1999.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Transendothelial migration of lymphocytes in chronic lymphocytic leukaemia is impaired and involved down‐regulation of both L‐selectin and CD23

Abstract: Summary.Chronic lymphocytic leukaemia (B-CLL) is characterized by a progressive accumulation of B lymphocytes in blood and bone marrow and high concentrations of soluble CD23 and L-selectin are found in the serum of these patients. In this study lymphocytes from normal subjects and patients with B-CLL were allowed to undergo transendothelial migration across confluent layers of human umbilical vein endothelial cells. Lymphocytes in B-CLL samples showed an impaired capacity to migrate while the minor proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 43 publications
(35 reference statements)
2
20
0
Order By: Relevance
“…The ability of matrix metalloprotease (MMP) inhibitors to markedly suppress P2X7R-dependent loss of surface CD62L from human B cells indicated that bona fide shedding of the ecto-domain is the predominant mechanism. P2X7R activation in human B cells and monocytederived dendritic cells has also been shown to elicit the shedding of CD23, an intrinsic plasma membrane protein that functions as a low-affinity receptor for IgE with links to chronic inflammatory diseases [22,23]. The ATPinduced loss of surface anti-CD23 epitopes was correlated with the extracellular accumulation of soluble CD23 protein which was suppressed in the presence of MMP inhibitors.…”
Section: P2x7r-mediated Regulation Of Plasma Membrane Composition Andmentioning
confidence: 99%
“…The ability of matrix metalloprotease (MMP) inhibitors to markedly suppress P2X7R-dependent loss of surface CD62L from human B cells indicated that bona fide shedding of the ecto-domain is the predominant mechanism. P2X7R activation in human B cells and monocytederived dendritic cells has also been shown to elicit the shedding of CD23, an intrinsic plasma membrane protein that functions as a low-affinity receptor for IgE with links to chronic inflammatory diseases [22,23]. The ATPinduced loss of surface anti-CD23 epitopes was correlated with the extracellular accumulation of soluble CD23 protein which was suppressed in the presence of MMP inhibitors.…”
Section: P2x7r-mediated Regulation Of Plasma Membrane Composition Andmentioning
confidence: 99%
“…5A). Expression of L-selectin, which is shed during transmigration and rapidly gained back in the lymph node after homing (29), among the transferred, labeled T cells was the same before and after the homing to lymph nodes. A comparison of Ly6C expression among the labeled cells that were found in various organs indicated that they homed equally well to lymph nodes, liver, and spleen (Fig.…”
Section: Ly6c Is Temporarily Lost From the Cell Surface Upon Homing Tmentioning
confidence: 99%
“…In contrast, oxidised ATP did not affect the loss of CD62L during CLL lymphocyte transmigration [69], suggesting P2X7 may not play a role in this process. This difference may be due to different experimental conditions including cell type and species.…”
Section: Cd62l (L-selectin)mentioning
confidence: 71%